Detention observed through the prism of human rights - Milošević, Dragana (Glasnik Advokatske komore Vojvodine, 2021)
The paper contains an analysis of the reasons for detention and its frequent application, all in the light of the European Convention of Human Rights and Fundamental Freedoms, with emphasis on Article 5. The human rights of detainees are analyzed, with special reference to detention. The reasons for requesting an extension of detention are important to consider carefully, as prolonged detention creates a breeding ground for human rights violations, and therefore urgent and efficient handling of detention cases is necessary. The paper analyzes the decisions of European Court of Human Rights and the Constitutional Court, which asessed the constitutionality and legality of the provisions governing detention, as well as the consideration of constitutional complaints.
Keywords: Detention; detention order; iterative danger; European Convention for the Protection of Human Rights and Freedoms; Human rights; European Court of Human Rights; Constitutional Court